Critical Analysis of Customs Digitalization-Customs Broker Perspective - John Pius; Sekar Murugan (Journal of Vasyl Stefanyk Precarpathian National University, 2025)
Customs digitalization has significantly transformed clearance procedures in international trade, moving from manual, paper-based processes to streamlined, risk-based, and digital systems. In India, this transformation has directly impacted the role of Customs House Agents (CHAs), who continue to play a vital intermediary role. This study examines two central aspects: (1) how digital customs initiatives—such as electronic filing, Risk Management Systems (RMS), single-window systems, and the Authorized Economic Operator (AEO) program—have influenced clearance efficiency, and (2) how the professional role of CHAs is evolving in response to these changes. Through qualitative research involving in-depth interviews with experienced, licensed CHAs, the study captures nuanced insights into the operational impact of digital systems and brokers’ adaptive strategies. Data were coded and thematically analysed using MAXQDA software, allowing for the systematic identification of key patterns and themes emerging from expert perspectives. Findings reveal that digitalization has led to a substantial reduction in physical intervention, simplified documentation requirements, and improved procedural transparency. However, CHAs remain indispensable due to their expertise in error-free digital document filing, coordinating during physical examinations, and providing export-import clearance guidance in compliance with customs regulations. These functions highlight the sustained strategic relevance of CHAs, especially in ensuring trade flow continuity and regulatory adherence. The paper recommends capacity-building initiatives and digital training programs for CHAs to strengthen their evolving role in a technology-driven customs environment. It also calls for policy frameworks that recognize and integrate the expertise of CHAs in shaping resilient and adaptive trade facilitation ecosystems.